THE HISTORY OF TRADE UNIONS OF PRINTING WORKERS - Абдукаримова М. И. (TARIXIY TADQIQOTLAR, 2025)
The article examines the formation and development of trade unions of printing industry workers in the territory of modern Uzbekistan. Particular attention is paid to the charter of the Trade Union of Printing Workers of Turkestan. The article provides an analysis of the key provisions of this charter.